Gender’s Moderating Role in Employee Satisfaction Determinants and Retention in Saudi Arabia’s Higher Education Sector - Alharthey , Abdullah Mulfi; Leong, Yee Choy; Said, Mohd Fuaad; Chong, Choo Wei (Advances in Social Sciences Research Journal, 2022)
Saudi Arabia’s higher education system suffers from academicians’ retention issues, besides low satisfaction. The employment situation in Saudi universities has shown considerable instability for many years, as shown by the high turnover rates among academic staff. The turnover rate is reported to be high and needs to be addressed with the help of retention strategies. Thus, the objective of this study is to identify and consolidate various relevant factors that have an impact on employee satisfaction and retention in the education sector in KSA, specifically in universities. This study also examines the mediating role of employee satisfaction between three factors: compensation package, perceived organizational support, and supportive work environment with regard to employee retention and the moderating role of gender between employee satisfaction and employee retention. To achieve the objectives, a survey strategy was applied to this study because it is associated with a deductive approach. This study employs the quantitative method, relying on primary data at the cross-sectional horizon. The population of this study comprises the academicians who work within Saudi Arabian universities. The online survey instrument was used to collect the data from the target sample size, which was determined to be 384 academicians. The study used structural equation modeling (SEM) to test the hypotheses developed in the study. The study has found a supportive work environment has a positive, significant relationship with employee satisfaction, as well as with employee retention. However, there were no relationships between (compensation package, perceived organizational support) and both employee satisfaction and employee retention. The study found employee satisfaction significantly mediated the relationship between a supportive work environment on employee retention. This study showed the importance of employee satisfaction in order to assist organizations in achieving employee retention. This study showed that the absence of moderator factors does not affect the relationship between employee satisfaction and employee retention.